A NEW SPECIES OF OPHIORRHIZA (RUBIACEAE) FROM GREAT NICOBAR ISLAND, INDIA - N. P. BALAKRISHNAN (Reinwardtia, 1980)
Ophiorrhiza nicobarica Balakr. is described and illustrated and com- pared with Ophiorrhiza trichocarpos Bl.